Toxoplasmosis: prevalence and risk factors - Nissapatorn, V.; Noor Azmi, M.A.; Cho, S.M.; Fong, Mun Yik; Ithoi, Init; Rohela, M.; Khairul Anuar, A.; Quek, K.F.; Latt, H.M. (Informa Healthcare, 2003)
The gene encoding the excretory-secretory antigen TES-120 of dog ascarid worm Toxocara canis was cloned into the bacterium Escherichia coli. The specificity of the recombinant TES- 120 antigen produced by the bacterium was investigated.A total of 45 human serum samples from patients infected with different helminthes and protozoa, including 8 cases of toxocariasis, were tested against the recombinant antigens in immunoblot assays. The results from the assays revealed that the recombinant TES-120 antigen reacted with sera from toxocariasis patients only. This highly specific recombinant TES-120 antigen can potentially be used for the development of an inexpensive serodiagnostic assay for human toxocariasis.